APOPTOSIS MARKERS IN NEWBORN CHILDREN WITH MILD HYPOXIC DAMAGE OF CNS - D.H. Posternak (Проблеми екології та медицини)
Perinatal hypoxic damage of CNS in newborns is the leading reason of high mortality and disability at children's age. However, there are difficulties in diagnostics, therapy and forecasting of result of hypoxemic injuries of the brain in newborn children. We have studied apoptosis markers in blood (level of the circulating fragmented DNA and DNA fragmentation in lymphocytes) in 36 full-term newborn patients with mild perinatal hypoxic damage of CNS whose gestational age was from 36 to 41 weeks. The control group included 20 healthy full-term children. We defined severity of hypoxic damage of the central nervous system, using the anamnesis of a disease, Apgar scale, clinical criteria, change of the neurologic status according to N. P. Shabalov, as well as neurosonography. Investigation phases of newborns were at the first, third and seventh day. In patients with mild hypoxic damage of the central nervous system the unidirectional dynamics of changes in all studied apoptosis markers was noted. Hence, the maximum growth of the circulating fragmented DNA by 8.6% and increase in level of DNA fragmentation in lymphocytes by 1.6 times were noted at the 3rd day of research. At the last stage, the tendency to decrease in indicators and return to initial figures was observed. It was followed by improvement of the neurologic status of newborns. Thus, dynamics of change in markers of apoptosis such as level of the circulating DNA and DNA fragmentation in lymphocytes in healthy newborns, demonstrates adaptation of patient’s body to the postnatal stress by the 7th day. Meanwhile, the unidirectional changes of levels of the studied indicators in newborns with mild hypoxic damage of CNS are reflected by the severity of brain damage, and also indicates adequacy of the chosen methods for the detection of apoptosis.